Sumbangan Ilmu Etnobotani dalam Memfasilitasi Hubungan Manusia dengan Tumbuhan dan Lingkungannya - Walujo, Eko Baroto (JURNAL BIOLOGI INDONESIA, 2011)
Ethnobotany Contributes to The Understanding Human Relationship with Plant and TheirEnvironment. The scope of ethnobotanical research has been developed to a broader scopefrom the originated word of ethnobotany was coined.. This discipline attempts to explainreciprocal relationships which occur between local societies and its natural world, in extant,between local societies and their cultures that reflected in the archeological records.Ethnobotany is also very closely related to the domestication of plants such as the speciesdomesticated, where these species domesticated, the purpose of domestication, the manner,and the status of the domesticated plants today. Etnobothany also concerns to the role ofplants in ecology, environment and phytogeography as conceived by tradition or by the localcommunities. In addition to its traditional role in economic botany and the exploration ofhuman cognition, ethnobotanical research has been applied to the practical areas such asbiodiversity prospecting and vegetation management. Thus ideally, ethnobotany shouldincludes rules and categorization acknowledged by local communities. Rules and categorizationare use to appropriately facing daily social situations in recognizing, interpreting and utilizingplant resources in their environment. In summary, the scope of research in ethnobotany isinterdisciplinary and ethnoscience as mentioned earlier and these scopes will be the mainfocus of discussion in this article. In particular, in its relation to the strategic position ofIndonesia based on wealth, diversity of plants, species and ecosystems and socio-culturallife.Key Words: Ethnobotany, Localknowledge, Wisdom